Analysis Of The Effect Of NPL, Der And Asset Growth On Banking Profitability Before & During Covid-19 Listed On Idx - Budhi Setiawan; Agus Rahman Alamsyah; Murtianingsih Murtianingsih (Publikasi Indonesia, 2023)
The COVID-19 virus threatens the safety of the public so the government takes the policy of PSBB or the policy of Large Scale Social Restriction that suppresses the Indonesian economy. Indonesia’s economic growth at the time of the COVID-19 pandemic underwent contractions that led to economic growth of only 2.07% from the average before COVID-19 above 5.00%. The performance of the Nasional Banking sector which is the pillar of the economy in Indonesia also affected the covid-19 pandemic. The general bank’s profitability statistics-ROA statistics released by the financial service authority during the COVID-19 pandemic experienced a significant decline, The average profitability of ROA before the COVID-19 pandemic of 2.5% down to 1.5% during the COVID-19 pandemic. Researchers compared the performance of national banking in this case the public bank over several independent variables against dependent variables before and during the covid-19 pandemic. The purpose of the research is: 1. To find out the influence of Non-Performing Loan (NPL) on profitability on national banking before and during the COVID-19 pandemic, 2. To find out the influence of Debt To Equity Ratio (DER) on the profitability of national banking before and during the COVID-19 pandemic, 3. To find out the influence of asset growth on profitability in national banking before and during the COVID-19 pandemic, 4. To find out the influence of Non-Performing Loan (NPL), Debt-to debt-equity ratio (DER), and asset growth simultaneously on profitability in national banking before and during the COVID-19 pandemic. The method used in this study is quantitative with secondary data sources.